Political Participation Of Beginning Voters In The Election Of Head Of Bangsri Village, Bulakamba Sub-District, Brebes District, In 2022 - Suparto, Diryo; Zarkasih Wisma Pamungkas, Muhammad (Pusat Publikasi Nusantara, 2023)
In 2022, Brebes Regency will carry out the 3rd stage of Simultaneous Village Head Elections, including in Bangsri Village, which involves the participation of Beginner Voters. Political participation is a form of citizen participation in the political process. In a democracy, the people are expected to actively participate in politics. The political participation of the Bangsri Village novice voters can be seen in various forms, including Pre-Election, During Election and Post-Election. Judging from the three forms of participation, the participation of novice voters in the Bangsri Village head election looks low. This study uses the theory of Political Participation (Gabriel Almond), namely the Conventional Political Participation Form, which is a normal and legal form of participation as a research analysis knife and as an instrument to conduct in-depth studies to determine the political participation of the Bangsri Village community. This study uses descriptive qualitative research methods. Descriptive analysis method is used to obtain a systematic, factual and accurate description of the facts, characteristics and relationships between the phenomena being investigated. The results of this study indicate that the Political Participation of Beginner Voters in the Election of the Bangsri Village Head, Bulakamba District in participation in the KPPS Committee and Officer, knowing DPT information, seeing the determination and taking of the serial number of the village head candidate, participating in the Timses of one of the candidates, participating in the campaign agenda , voting, and watching the vote count is still considered low. There are several factors that cause the political participation of novice voters is still low, namely the heavy factor in work, heavy on school, wandering, and lack of experience. So that the political participation of novice voters in Bangsri Village is still not maximized.